Objective corruption risks – subjective controls: Integrity of Publicly Owned Business Associations, Methodology and Results of the Integrity Survey - Pulay, Gyula Zoltán; Lucza, Anikó (Public Finance Quarterly, 2023)
In 2017, the State Audit Office of Hungary repeatedly surveyed the integrity of publicly owned business association. Survey data show that the degree of corruption risks at these companies depends essentially on objective factors such as company size, provision of public services, and the amount of public funds used. On the other hand, the strength of the integrity control systems put in place to prevent these risks primarily depends on the owner and/or management of the business association, i.e. on subjective factors. The business associations with the best level of integrity stood out from the rest by carrying out systemic risk analyses and risk management, which also included surveying corruption risks. The survey also confirmed that the level of integrity controls is significantly above average in companies with an independent internal audit function operating in accordance with the professional standards.